NMR metabolomics highlights sphingosine kinase‐1 as a new molecular switch in the orchestration of aberrant metabolic phenotype in cancer cells. Issue 5 (30th March 2017) - Bernacchioni, Caterina; Ghini, Veronica; Cencetti, Francesca; Japtok, Lukasz; Donati, Chiara; Bruni, Paola; Turano, Paola
Abstract : Strong experimental evidence in animal and cellular models supports a pivotal role of sphingosine kinase‐1 (SK1) in oncogenesis. In many human cancers, SK1 levels are upregulated and these increases are linked to poor prognosis in patients. Here, by employing untargeted NMR‐based metabolomic profiling combined with functional validations, we report the crucial role of SK1 in the metabolic shift known as the Warburg effect in A2780 ovarian cancer cells. Indeed, expression of SK1 induced a high glycolytic rate, characterized by increased levels of lactate along with increased expression of the proton/monocarboxylate symporter MCT1, and decreased oxidative metabolism, associated with the accumulation of intermediates of the tricarboxylic acid cycle and reduction in CO2 production. Additionally, SK1‐expressing cells displayed a significant increase in glucose uptake paralleled by GLUT3 transporter upregulation. The role of SK1 is not limited to the induction of aerobic glycolysis, affecting metabolic pathways that appear to support the biosynthesis of macromolecules. These findings highlight the role of SK1 signaling axis in cancer metabolic reprogramming, pointing out innovative strategies for cancer therapies. Abstract : The high mortality rate for ovarian cancer is mainly due to the development of resistance to chemotherapeutic drugs. Chemoresistance relies on complex molecular mechanisms that determine increased drug efflux, metabolic switch, drug inactivation, and deregulation of apoptosis. Here, we demonstrate that sphingosine kinase‐1 (SK1), previously reported as key modulator of chemoresistance, causes a metabolic shift toward aerobic glycolysis, conferring growth advantages to tumor cells. Thus, SK1 is proposed as a novel potential target to antagonize the metabolic shift accompanying oncogenesis.